2013
DOI: 10.4236/ojcd.2013.34035
|View full text |Cite
|
Sign up to set email alerts
|

Public health aspects of visceral leishmaniasis in Montenegro

Abstract: Leishmaniasis belongs to the parasitic communicable zoo noses, caused by members of Leishmania species.The infected phlebotomies sand fly carries the parasites, which cause the different forms of disease. Retrospective/prospective review of records for documented cases of visceral leishmaniasis (VL) in period from 1992 to 2012 in Montenegro shows 83 diagnostic cases, and 1 (1.20%) case with dermal leichmaniasis. with 3 (3.61%) deaths cases. Analyses of age show: 36 (43.37%) children and 47 (56.63%) adults. Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Based on epidemiological studies, the extension of endemic focus of leishmaniasis in our environment is evident, based on the number of registered cases in nonendemic areas of Montenegro. Veterinary studies of domestic and stray dogs from different parts of Montenegro confirmed their high level of infection with Leishmania parasites up to 83% [16].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on epidemiological studies, the extension of endemic focus of leishmaniasis in our environment is evident, based on the number of registered cases in nonendemic areas of Montenegro. Veterinary studies of domestic and stray dogs from different parts of Montenegro confirmed their high level of infection with Leishmania parasites up to 83% [16].…”
Section: Discussionmentioning
confidence: 84%
“…Veterinary service does not have data on the prevalence of infections in dogs in Montenegro. Numerous human cases have been reported for the European Union [16,17,18,19]. In 1999, most reported cases originated from the Mediterranean area, where Dirofilaria spp.…”
Section: Discussionmentioning
confidence: 99%
“…76 cases originated from central parts of the country – Podgorica (most affected), Cetinje, Danilovgrad and Nikšić municipalities, and 6 cases occurred in mountain regions of Bijelo Polje, Berane, Plav and Rožaje municipalities [24]. In the 1992–2012 period 83 cases of VL were recorded [25]: 36 cases (43.37%) in children and 47 (56.63%) in adults.…”
Section: Resultsmentioning
confidence: 99%
“…It is also thought to be endemic in Romania, Bosnia, Macedonia, Montenegro and Bulgaria (Diza, 2008;Tsatchev et al, 2010;Alvar et al, 2012;Andric et al, 2013;Mircean et al, 2014).…”
Section: Geographical Distribution Of Canl In Europementioning
confidence: 99%